2000
DOI: 10.1021/bk-2000-0757.ch003
|View full text |Cite
|
Sign up to set email alerts
|

Development of Process Chemistry for the Removal of Cesium from Acidic Nuclear Waste by Calix[4]arene-crown-6 Ethers

Abstract: A solvent suitable for extracting cesium from acidic nitrate media, such as that stored at the U.S. Department of Energy's Idaho National Engineering and Environmental Laboratory (INEEL), has been developed. The solvent possesses good chemical stability, displays excellent cesium selectivity, and provides good extraction and stripping performance with satisfactory phase-coalescence behavior. The calix[4]arene-crown-6 ether used in this solvent (1,3-alt-bis-n-octyloxycalix[4]arene-benzo-crown-6) was selected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…As a consequence of the high degree of degradation observed in dodecane, the impact of nitric acid was evaluated only in NPOE solvent. In the presence of 3 M HNO 3 , the surviving amount of (octMC6-H) decreased (27% more loss) 16,18 and these losses probably correspond to the production of the nitro compounds. For this purpose, octMC6-NO 2 and octMC6-(NO 2 ) 2 were determined by external standard calibration by measuring the areas of the LC peaks vs. concentration at their maximum wavelengths.…”
Section: Aromatic Substitutionmentioning
confidence: 95%
See 1 more Smart Citation
“…As a consequence of the high degree of degradation observed in dodecane, the impact of nitric acid was evaluated only in NPOE solvent. In the presence of 3 M HNO 3 , the surviving amount of (octMC6-H) decreased (27% more loss) 16,18 and these losses probably correspond to the production of the nitro compounds. For this purpose, octMC6-NO 2 and octMC6-(NO 2 ) 2 were determined by external standard calibration by measuring the areas of the LC peaks vs. concentration at their maximum wavelengths.…”
Section: Aromatic Substitutionmentioning
confidence: 95%
“…14,15 Extensive experiments in the nuclear industry with solvent systems indicate that the degradation of solvent due to exposure to radiolysis, and to a lesser extent hydrolysis, can significantly degrade its performance. Therefore, before developing an extraction process, 16 the radiolytic stability of the system and the characterisation of the degradation products must be investigated. The stability of some calixarene molecules towards nitric acid media and/or radiolysis has already been reported.…”
mentioning
confidence: 99%
“…[1] Molecular cages based on transition-metal vertices often easily self-assemble, and those with inorganic frameworks are of special interest because their rigidity, uncommon in organic ligands, [2][3][4][5] could give rise to high selectivity with respect to guest size.Prussian Blue (PB) and its variants [6][7][8] are insoluble cyanometallate polymers consisting of boxlike subunits that exhibit ion-exchange behavior. We and others have previously described molecular PB analogues with encapsulated cations.…”
mentioning
confidence: 99%
“…Oak Ridge National Laboratory researchers also investigated various calix [4]arene-crown ethers for potential use on INEEL acidic tank waste [89]. This work demonstrated that these extractants are highly effective at removing cesium from acidic media.…”
Section: Calixarenes/calixarene-crown Ethersmentioning
confidence: 99%